l
m + t = 20
11m + 3t = 100
Equation 1 is in the correct format.
Equation 2 is in the correct format.
11m + 3t = 100
11m + 3t - 3t = 100 - 3t
11m = 100 - 3t
11m | |
11 |
= |
100 - 3t |
11 |
m = | 100 - 3t |
11 |
1(m) + t = 20
1 * ((100 - 3t)/11) + t = 20
((100 - 3t)/11) + t = 20
11 * (((100 - 3t)/11) + t = 20)
11 * (((100 - 3t)/11) + t = 20)
100 - 3t + 11t = 220
-3t + 11t = 220 - 100
8t = 120
8t | |
8 |
= |
120 |
8 |
t = | 120 |
8 |
t = 15
1m + 1(15) = 20
1m + 15 = 20
1m = 20 - 15
1m = 5
1m | |
1 |
= |
5 |
1 |
m = | 5 |
1 |
m = 5
Math is always fascinating! Have you noticed? On the path to discovering the ultimate mysteries of math, we move forward with small steps.